Question
upstudy study bank question image url

\( 3 x+4 y=-24 \) and \( 7 x-4 y=-16 \)

Ask by Carlson Guzman. in South Africa
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( x=-4 \) and \( y=-3 \).

Solution

Solve the system of equations \( 3x+4y=-24;7x-4y=-16 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}3x+4y=-24\\7x-4y=-16\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=-\frac{24+4y}{3}\\7x-4y=-16\end{array}\right.\) - step2: Substitute the value of \(x:\) \(7\left(-\frac{24+4y}{3}\right)-4y=-16\) - step3: Multiply the terms: \(-\frac{7\left(24+4y\right)}{3}-4y=-16\) - step4: Multiply both sides of the equation by LCD: \(\left(-\frac{7\left(24+4y\right)}{3}-4y\right)\times 3=-16\times 3\) - step5: Simplify the equation: \(-168-40y=-48\) - step6: Move the constant to the right side: \(-40y=-48+168\) - step7: Add the numbers: \(-40y=120\) - step8: Change the signs: \(40y=-120\) - step9: Divide both sides: \(\frac{40y}{40}=\frac{-120}{40}\) - step10: Divide the numbers: \(y=-3\) - step11: Substitute the value of \(y:\) \(x=-\frac{24+4\left(-3\right)}{3}\) - step12: Substitute back: \(x=\frac{-24+4\times 3}{3}\) - step13: Calculate: \(x=-4\) - step14: Calculate: \(\left\{ \begin{array}{l}x=-4\\y=-3\end{array}\right.\) - step15: Check the solution: \(\left\{ \begin{array}{l}x=-4\\y=-3\end{array}\right.\) - step16: Rewrite: \(\left(x,y\right) = \left(-4,-3\right)\) The solution to the system of equations \(3x+4y=-24\) and \(7x-4y=-16\) is \(x=-4\) and \(y=-3\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To solve the system of equations, you can use the method of elimination or substitution. If you choose elimination, you can add the two equations directly: 1. \( 3x + 4y = -24 \) 2. \( 7x - 4y = -16 \) Adding these gives you \( 10x = -40 \), so \( x = -4 \). Next, plug \( x = -4 \) back into either equation to find \( y \): Using the first equation: \( 3(-4) + 4y = -24 \) leads to \( -12 + 4y = -24 \), thus \( 4y = -12 \) and \( y = -3 \). So the solution is \( x = -4 \) and \( y = -3 \). Solving systems of equations might seem daunting, but it’s like a puzzle! It’s all about finding where the lines (or equations) intersect. No secret detective skills necessary—just a bit of number crunching! Making a common mistake involves misreading signs when adding or subtracting equations. Always double-check if you're applying the right operation! Mistakes like these can lead to incorrect solutions. So, when in doubt, check every step to ensure your calculations are spot on!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy